The Role Of Oversight And Anti-corruption In Reforming The Public Sector In Algeria And Establishing Governance - قادري, فوزي (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
Since the nineties, the public sector in Algeria has witnessed a continuous decline as a result of the spread of corruption. Acknowledgment by the Algerian authorities of this critical situation, and their desire to perpetuate the requirements of governance given its ability to reverse the situation, by relying on two pillars, namely, to activate the role of each of the oversight and the fight against corruption, for this reason, it approved a large arsenal of legal texts, the latest of which was the constitutional amendment of 2020, supported by the establishment of a diverse institutional system that implements these legal texts on the ground, with the aim of discovering the imbalances taking place, as well as combating corruption and punishing the corrupt, which allows creating a solid ground for devoting the requirements of governance and advancing the reality of the public sector in Algeria.